2006
DOI: 10.1051/0004-6361:20053467
|View full text |Cite
|
Sign up to set email alerts
|

Properties of dust in the high-latitude translucent cloud L1780

Abstract: We have analyzed the properties of dust in the high galactic latitude translucent cloud Lynds 1780 using ISOPHOT maps at 100 µm and 200 µm and raster scans at 60 µm, 80 µm, 100 µm, 120 µm, 150 µm and 200 µm. In far-infrared (FIR) emission, the cloud has a single core that coincides with the maxima of visual extinction and 200 µm optical depth. At the resolution of 3.0 , the maximum visual extinction is 4.0 mag. At the cloud core, the minimum temperature and the maximum 200 µm optical depth are 14.9 ± 0.4 K and… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
44
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
8
1

Relationship

6
3

Authors

Journals

citations
Cited by 42 publications
(50 citation statements)
references
References 31 publications
6
44
0
Order By: Relevance
“…The value of dust opacity is uncertain and is observed to vary from region to region (e.g. Kramer et al 2003;Stepnik et al 2003;Lehtinen et al 2004Lehtinen et al , 2007Ridderstad et al 2006;Martin et al 2012). In diffuse medium the expected value of κ is lower by a factor of two (Boulanger et al 1996).…”
Section: Column Density Maps and Massesmentioning
confidence: 99%
“…The value of dust opacity is uncertain and is observed to vary from region to region (e.g. Kramer et al 2003;Stepnik et al 2003;Lehtinen et al 2004Lehtinen et al , 2007Ridderstad et al 2006;Martin et al 2012). In diffuse medium the expected value of κ is lower by a factor of two (Boulanger et al 1996).…”
Section: Column Density Maps and Massesmentioning
confidence: 99%
“…The observed changes in the dust opacity at long wavelengths might be evidence for changes in the dust properties, suggesting that these changes occur due to the accretion of mantles (del Burgo et al 2003;Kiss et al 2006) and grain coagulation (Bernard et al 1999;del Burgo et al 2003;Stepnik et al 2003; Kiss et al 2006;Ridderstad et al 2006;Paradis et al 2009). Gas accretion forms grain mantles composed mainly of water ice and other molecular species (e.g.…”
Section: Introductionmentioning
confidence: 98%
“…Lagache et al 1998;Bernard et al 1999;Stepnik et al 2003;del Burgo et al 2003;Planck Collaboration 2011b). Additionally, an increase in the dust opacity by a factor between 2 and 4 is observed in these denser regions at long wavelengths, which is inferred from the low dust temperature, and not always by comparison to the gas or A V (Bernard et al 1999;Hotzel et al 2001;Cambrésy et al 2001;Stepnik et al 2003;Bianchi et al 2003;del Burgo et al 2003;del Burgo & Laureijs 2005;Kiss et al 2006;Lehtinen et al 2007;Ridderstad et al 2006;Bot et al 2009;Paradis et al 2009;Planck Collaboration 2011b). Moreover, the abundance of the very small grains (VSGs, 1−15 nm in radius), that are stochastically heated and responsible for the 60 μm emission, decreases by ∼80-100% in the transition from diffuse to dense molecular clouds (Laureijs et al 1991;Abergel et al 1994Abergel et al , 1996Lagache et al 1998;Stepnik et al 2003;Kramer et al 2003).…”
Section: Introductionmentioning
confidence: 99%
“…An increase of the dust emissivity by a factor of 3 compared to the standard diffuse value was needed to reproduce the cold temperatures observed in the Taurus filament L1506 (Stepnik et al 2003). In dense regions, several studies have shown an opacity increase by a factor between 2 to 4 (Cambrésy et al 2001;Kramer et al 2003;Bianchi et al 2003;del Burgo et al 2003;Kiss et al 2006;Ridderstad et al 2006;Lehtinen et al 2007). More recently, similar results have been obtained with Herschel and Planck in molecular clouds and cold cores Planck Collaboration XXV 2011;Martin et al 2012;Roy et al 2013).…”
Section: Introductionmentioning
confidence: 99%